An unusual case of obstructive airway disease spectrum - Dhwani J. Patel; Grinish Tamakuwala; Parul Vadgama (The Journal of Association of Chest Physicians)
Bronchial anthracofibrosis (BAF) is a rare clinical condition affecting the lungs. It was described back in 1998 in Korea, in association with tuberculosis. In the recent studies, it has been observed that BAF is strongly associated with long-standing exposure to biomass fuels and mostly affecting elderly females. Most of the reported cases till date are seen in patients belonging to the older age group. Hereby, we are reporting a case of a female patient who presented with BAF at a very young age. Due to the lack of awareness among treating physicians and even pulmonologists, BAF remains underdiagnosed and hence we can expect, whatever we are seeing is just the tip of an iceberg.